At-CycD2 Enhances Accumulation of Above-Ground Biomass and Recombinant Proteins in Transgenic Nicotiana benthamiana Plants - Kopertekh, Lilya; Reichardt, Sven (Frontiers in Plant Science, 2021)
Transient expression in Nicotiana benthamiana holds great potential for recombinant protein manufacturing due to its advantages in terms of speed and yield compared to stably transformed plants. To continue improving the quantity of recombinant proteins the plant host will need to be modified at both plant and cellular levels. In attempt to increase leaf mass fraction, we transformed N. benthamiana with the At-CycD2 gene, a positive regulator of the cell cycle. Phenotypic characterization of the T1 progeny plants revealed their accelerated above-ground biomass accumulation and enhanced rate of leaf initiation. In comparison to non-transgenic control the best performing line At-CycD2-15 provided 143% and 140% higher leaf and stem biomass fractions, respectively. The leaf area enlargement of the At-CycD2-15 genotype was associated with the increase of epidermal cell number compensated by slightly reduced cell size. The production capacity of the At-CycD2-15 transgenic line was superior to that of the non-transgenic N. benthamiana. The accumulation of transiently expressed GFP and scFv-TM43-E10 proteins per unit biomass was increased by 138.5% and 156.7%, respectively, compared to the wild type. With these results we demonstrate the potential of cell cycle regulator gene At-CycD2 to modulate both plant phenotype and intracellular environment of N. benthamiana for enhanced recombinant protein yield.